(untitled) (Health Renaissance, 2012)
Background: The practice of blood ordering before surgery is usually excessive. Hazards of over ordering include burden to blood banking, outdating of blood, unnecessary wastage of hospital resources, mental and physical stress to patient party. A study on blood ordering practice provides important feedback for improvement of blood ordering service system and developing Maximum Surgical Blood Ordering Schedule (MSBOS). Objectives: To find out the ratio between cross-matched and transfused blood units (C:T ratio) in routine operation theatres (OT) of BP Koirala Institute of Health Sciences (BPKIHS) and the time lag between blood demand and arrival in the OTs. Methods: Data of 94 patients undergoing elective surgery with potential need for blood transfusion over the period of one month were collected and analyzed prospectively. The variables noted include age, gender, body weight, blood group, hemoglobin level, diagnosis, type of surgery, maximum allowable blood loss, actual blood loss; number of blood units cross-matched and actually transfused. Results: Altogether, 161 blood units were cross matched and only 24 of them were transfused making the C:T ratio of 6.7:1. Fourteen out of 24 units were transfused only in gynecological & obstetrical patients. The mean time interval between the demand and the arrival of blood units was 10 ± 7.6 minutes. Conclusion: The overall C:T ratio in the routine OT of BPKIHS is comparatively high. Further study with larger sample size is needed for recommending MSBOS. DOI: http://dx.doi.org/10.3126/hren.v10i2.6583 Health Renaissance 2012; Vol 10 (No.2); 137-138